Corporate Criminal Liability in Corruption Crimes: A Philosophical Study and Law Enforcement Practice - Mario Randy Lengkong; Ismiati Essing (PT. NALURI EDUKASI PRESS, 2026)
This study aims to examine the philosophical construction of corporate criminal liability in corruption crimes and analyze its law enforcement practices in Indonesia. The method used is a qualitative approach with a literature review, through content analysis of criminal law literature, court decisions, laws and regulations, and reports from law enforcement agencies systematically obtained from scientific baseline data. The results of the study indicate that philosophically, corporations can be held criminally liable based on the theory of internal decision structures, the communicative theory of punishment, and the progressive legal approach. Normatively, Indonesia has adequate legal instruments, but their enforcement is hampered by the complexity of proving corporate mens rea, the lack of standardized technical guidelines for collection, and cultural institutional barriers. Comparison with the practices of the United States, Singapore, and South Korea demonstrates the importance of synergy between political commitment, institutional capacity, and a culture of corporate accountability.